1998
DOI: 10.1001/archpsyc.55.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and Glial Somal Size in the Prefrontal Cortex

Abstract: Distinct cytometric abnormalities support the hypothesis that neuronal degeneration in the prefrontal cortex is not a prominent feature of the neuropathological changes in schizophrenia, although an ongoing process in Huntington disease. Rather, schizophrenia appears to involve more subtle abnormalities, with the largest corticocortical projection neurons of layer IIIc expressing the greatest somal reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(104 citation statements)
references
References 33 publications
10
93
0
1
Order By: Relevance
“…The sharp increase in HVC neuronal density within 12 h of T withdrawal suggests that there is substantial degeneration of dendritic and/or axonal processes. In patients afflicted with schizophrenia, neuropil degeneration is correlated with an increase in neuronal density and decrease in somatic area (54)(55)(56) and is regulated by apoptotic mechanisms (57). Neuropil degeneration can occur quickly; dendrites of dentate gyrus neurons show signs of degeneration within hours of status epilepticus (58), and deafferentation leads to rapid atrophy of dendritic arbors within hours (59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…The sharp increase in HVC neuronal density within 12 h of T withdrawal suggests that there is substantial degeneration of dendritic and/or axonal processes. In patients afflicted with schizophrenia, neuropil degeneration is correlated with an increase in neuronal density and decrease in somatic area (54)(55)(56) and is regulated by apoptotic mechanisms (57). Neuropil degeneration can occur quickly; dendrites of dentate gyrus neurons show signs of degeneration within hours of status epilepticus (58), and deafferentation leads to rapid atrophy of dendritic arbors within hours (59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study based on human post mortem tissue indicated that the somas of neuronal cells are 4.7-22.4 lm in diameter, while the somas of glial cells are only 2.6-8.7 lm in diameter. 29 Although there is a size overlap (4.7-8.7 lm) between these two kinds of cells, there is a significant difference in size between neurons and glial cells, so by selecting a suitable flow condition, neuronal cells experience a dominant secondary flow drag and can be focused at the centre of the serpentine channel. Moreover, glial cells simultaneously experience a dominant inertial lift force and focus at the two sidewalls, and therefore neurons and glial cells can be separated efficiently by collecting the corresponding particle streams, as shown schematically in Fig.…”
Section: B Mechanismmentioning
confidence: 99%
“…[1][2][3] Complementary functional brain imaging studies indicate impaired connectivity between the frontal lobe and other brain regions in both disorders. 4 At the cellular and molecular level, postmortem histopathologic studies of the frontal lobe in schizophrenia demonstrated reduced neuronal size, 5 decreased density of dendritic spines, 6,7 and altered synaptic protein immunoreactivity or mRNA levels. [8][9][10][11] These observations suggest that abnormal synaptic connectivities are involved in the pathophysiology of schizophrenia and other neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%